Fluxo gênico de soja geneticamente modificada, em semeaduras de verão e de inverno, com isolamentos de soja ou milho - Zanetti, Ana Luísa (2010)
Genetically modified soybean, tolerant to glyphosate, expanded its growing area in few years becoming the most sown in the country. The advantages of its use are many compared to the conventional soybean, which has led soybean farmers to prefer it. However, since some markets still prefer conventional soybean and its production occurs in smaller areas, there is the need to supply the market with high genetic quality seeds. The contamination of conventional seed lots with transgenic seeds has occurred with high frequency, in many stages of the production chain. One of the possibilities is the contamination by natural crossing between conventional plants and transgenic ones, in seed production fields. Therefore, this study evaluated the efficacy of the use of isolation barriers with soybean and maize plants, as well as gene flow of a transgenic cultivar to a conventional one, in summer and winter crops. The cultivars used were conventional MG/BR 46 [Conquista] and transgenic BRS Valiosa RR. The field experiments consisted of the combination of the use of two kinds of physical isolation (soybeans or maize) with two sowing dates (summer and winter), in a total of four experiments. The summer experiments were done at Getúlio Vargas Experimental Farm, of EPAMIG, in Uberaba, MG, and the winter ones at Suçuarana Farm, in São Romão, MG. The field trials were characterized by sowing a 6.5-m-sided square with the transgenic cultivar, isolated on all sides by 3 m cultivated with maize plants or the conventional soybean, and sided by 8 m of conventional soybeans. The experimental unit consisted of a 6.5 m long row of the conventional cultivar, at distances of 0.5, 1, 2, 4, 6 and 8 meters, counted from the last isolation line. The seeds were harvested, and 200 g of each experimental unit were used for transgenic soybean detection bioassay at the Laboratório de Ensino de Sementes of ICIAG, UFU, while the remainder was sown in the field. Before flowering, the plants were desiccated with Roundup (Glyphosate 3 L ha-1). The surviving transgenic plants were counted and their frequency calculated. For the bioassay, the seeds were pre-soaked in a glyphosate solution (0.6% e.a.) for 16 hours before the germination test and evaluated on the 5th day, determining the frequency of normal and abnormal seedlings. It was concluded that: a) the frequency of transgenic plants was greater in winter sowings than in the summer, regardless of the barrier used; b) the gene flow was reduced with increase distance in all of the experiments; c) the 11 m distance was not sufficient to avoid gene flow, and, d) the bioassay was not effective in quantifying the gene flow.